Properties of a Laminated Wood Composite Produced with Thermomechanically Treated Veneers - Larissa M. Arruda; Cláudio H. S. Del Menezzi (Advances in Materials Science and Engineering)
The paper aimed at evaluating the properties of plywood made from thermomechanically treated wood veneers. Veneers from Amescla (Trattinnickia burseraefolia) wood were treated in a hydraulic press with electric resistance heating. Two temperature levels were applied, 140°C and 180°C, for 1 and 2 minutes with 2.7 N/mm2 of pressure. A total of 30 plywood boards were produced, including six boards produced from untreated veneers. The results showed that the thermomechanical treatment did not have any deleterious effect on glue line strength and most of the mechanical properties of plywood made from treated veneers were improved. On the other hand, plywood made from untreated veneers presented better dimensional stability. Dimensional stability properties were most affected by the temperature of the treatment, while mechanical stability, represented by the glue line shear strength, was positively affected by temperature and duration of the treatment.